Neighborhood Environment and Urban Schoolchildren’s Risk for Being Overweight - Whitaker, Damiya (Am J Health Promot, 2013)
PURPOSE. Child and adolescent obesity is increasingly prevalent and predisposes risk for poor physical and psychosocial health. Physical and social factors in the environment, such as neighborhood disorder, may be associated with childhood obesity. This study examines the association between living in a disordered neighborhood and being overweight among a sample of urban schoolchildren. DESIGN. Baseline interview data, including height, weight, and hip circumference, were obtained from 313 elementary school-aged participants in a community-based epidemiologic study. SETTING. The setting was Baltimore, Maryland, a large metropolitan city. SUBJECTS. Subjects were elementary school students ages 8 to 12 years. MEASURES. To assess neighborhood characteristics, independent evaluators conducted objective environmental assessments using the Neighborhood Inventory for Environmental Typology instrument on the block faces (defined as one side of a city block between two intersections) where the children resided. ANALYSIS. Logistic regression models with generalized estimating equations were used to examine the association between neighborhood disorder and children being overweight. RESULTS. Neighborhood disorder showed a trend toward a statistically significant association with being overweight during childhood (odds ratio [OR], 1.03; confidence interval [CI], .99–1.07; p = .07) in the unadjusted model. Gender was significantly associated with being overweight, with female gender increasing the odds of being overweight by 50% in the sample (OR, 1.50; CI, 1.18–1.92; p < .01). After controlling for race, age, and comparative time spent on a sport, multivariable analyses revealed that gender (adjusted odds ratio [AOR], 2.42; CI, 1.63–3.59; p < .01) and neighborhood disorder (AOR, 1.09; CI, 1.03–1.15; p < . 01) were associated with being overweight. Further, an examination of interactions revealed girls (AOR, 2.40; CI, 1.65–3.49; p < .01) were more likely to be overweight compared with boys (AOR, 2.20; CI, 1.57–3.11; p < .01) living in neighborhoods with the same level of neighborhood disorder. CONCLUSION. Results suggest neighborhood hazards warrant additional consideration for their potential as obesogenic elements affecting gender-based disparities in weight among urban schoolchildren. Future studies in this area should include longitudinal examinations. (Am J Health Promot 2013;27[6]:410–416.)